A survey on intelligent system application to fault diagnosis in electric power system transmission lines - Ferreira, V.H.; Zanghi, R.; Fortes, M.Z.; Sotelo, G.G.; Silva, R.B.M.; Souza, J.C.S.; Guimarães, C.H.C.; Gomes, S. (Electric power systems research, 2016)
•A review on intelligent systems application to transmission line fault diagnosis.•The classification of strategies employed and their relationships with classical techniques are presented and discussed.•The main trends and research areas related to transmission line intelligent fault diagnosis systems are highlighted. Fault analysis and diagnosis constitute a relevant problem in power systems, with important economic impacts for operators, maintenance agents and the power industry in general. This has motivated the research and development of new algorithms and methods to address this problem. Intelligent systems have been proposed in the literature to deal with this problem in a significant number of applications. In the context of fault diagnosis in electric power systems, this survey presents a review of intelligent systems application to fault diagnosis in electric power system transmission lines. A huge number of related works can be found in the literature, being the major contributions reported in international journals. Then, the works cited in the present survey are restricted to those reported in regular journals that present high adherence to the aforementioned subject. The classification of strategies employed and their relationships with classical techniques are presented and discussed, allowing the identification of the main trends and research areas related to transmission line intelligent fault diagnosis systems.